Case Study from Israel-Augmenting Bee Flora to Sustain Honey Production - Gogate, Madhav (Indian Forester, 2016)
India has long tradition of obtaining honey from wild bees but in the context of landscape level forest resource planning and management, it has not received due recognition; honey collection is treated as a minor forest product. With a paradigm shift in forest resource ownership towards forest dwellers, who by default practice eco friendly cultivation on marginal land holdings that have sub-optimal production potentials. Apiculture practices on such lands are expected to provide not only boost in agri/horti production but also provide an additional income generation activity. As Israel is reported to have introduced exotic eucalypts from Australia to augment bee flora for optimizing honey bee products, a study tour was made for its appraisal and relevance in our context. Field visits and dialogue with representative major key stake holders/facilitators/researchers etc, confirmed the success. Similar concerted effort involving local stake holders, for multi-locations pilot scale, species trials with indigenous species as control are recommended.